Kontribusi Majelis Ta’lim Noto Jiwo Dalam Menanamkan Nilai-nilai Keagamaan Islam Bagi Jamaah Di Tengah Masyarakat Non-Muslim Di Jalan Tri Tunggal Kelurahan Karangpacar Bojonegoro - Ulva Badi’ Rohmawati, Fahru Rozi, Farida Isroani, Lailatul Fitriyah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Majelis Ta'lim is a non-formal community-based Islamic educational institution. Likewise with the Ta'lim Noto Jiwo Assembly in which there is a process of planting Islamic religious values. The community around the neighborhood is not only Muslim, but there are also non-Muslim communities, as well as the number of lay people about Islamic science, so that Islamic science is less desirable by the surrounding community. This research aims to find out the contribution of Ta'lim Noto Jiwo Assembly in instilling Islamic religious values for pilgrims, as well as to explain supporting factors and inhibiting the implementation of Ta'lim Noto Jiwo Assembly in the process of instilling Islamic religious values for worshippers in non-Muslim communities. This research uses a qualitative approach. The data collection is done with in-depth interview techniques, participatory observations, and documentation. The results of the analysis of data in this study showed that the Ta'lim Assembly contributed well in instilling Islamic religious values for worshippers in non-Muslim communities, by finding supporting factors and inhibitory factors in its implementation.